Pathways involved in the relationship between resilience and cognitive function: The Memento cohort: Epidemiology: Lifestyle risk factors. (7th December 2020) - Grasset, Leslie; Chêne, Geneviève; Dubois, Bruno; Vellas, Bruno; Pasquier, Florence; Blanc, Frédéric; Paquet, Claire; Hanon, Olivier; Gabelle, Audrey; Ceccaldi, Mathieu; Annweiler, Cedric; Salmon, Pierre Krolak; et al.
Abstract: Background: Given the burden related to dementia, identifying prevention targets against cognitive aging and Alzheimer's disease (AD) and related disorders is of high interest. While factors of resilience, i.e. education, physical or cognitive activity, or social network, are thought to mitigate the effect of cerebral damage on cognition, mechanisms involved are not well understood. This work thus aims to investigate the pathways involved in the association between resilience and cognition. Method: Data were collected as part of the Memento study, a French nationwide cohort including patients from 28 memory clinics with either isolated cognitive complaints or mild cognitive impairment. Factors contributing to resilience, such as education level, salary, physical activity, leisure activities, or social network, as well as MRI markers of brain health were collected at baseline. AD cerebrospinal fluid (CSF) biomarkers were assessed in a subsample (n=410). Based on resilience factors, we established a global resilience score using a latent variable from a structural equation model. Structural equation models were also used to evaluate cross‐sectional pathways between resilience, brain ageing biomarkers in relation to cognition, taking into account potential confounders (Figure). Estimates from latent variables were standardized and results reported are for one SD of resilience. Result: Participants' mean age was 70.9 years old, 62% were women, 28% were APOE‐ε4 carriers, and 59% had a CDR score of 0.5. Resilience score obtained for each participants, ranged from ‐2.28 to 2.73. AD CSF biomarkers were all significantly associated with worse cognition. Higher resilience was significantly associated with higher cognitive performances (total βres_cog =0.569, p<.0001). In addition to a direct effect on cognition (direct βres_cog =0.519, p<.0001), this association was partly mediated by an indirect effect of resilience on cognition (indirect βres_cog =0.050, p<.0001) through lower neurodegeneration (direct βres_nd =‐0.128, p<.0001). White matter hyperintensities volume, CSF Aβ42/Aβ40 ratio, and CSF phosphorylated tau were not involved in the association between resilience and cognition. Conclusion: Resilience preserves cognitive functions both directly and indirectly through an apparent protection against neurodegeneration. Beside, AD and small vessel disease markers are not associated with resilience and they do not mediate the protective effect of resilience on cognition.